Tubulin–Na + , K + ‐ATPase interaction: Involvement in enzymatic regulation and cellular function - Santander, Verónica Silvin (2018)
A new function for tubulin was described by our laboratory: acetylated tubulin forms a complex with Na+,K+-ATPase (NKA) and inhibits its activity. This process was shown to be a regulatory factor of physiological importance in cultured cells, human erythrocytes and several rat tissues. Formation of the acetylated tubulin/NKA complex is reversible. We demonstrated that in cultured cells, high concentrations of glucose induce translocation of acetylated tubulin from cytoplasm to plasma membrane with a consequent inhibition of NKA activity. This effect is reversed by adding glutamate, which is co-transported to the cell with Na+. Another post-translational modification of tubulin, detyrosinated tubulin, is also involved in the regulation of NKA activity: it enhances the NKA inhibition induced by acetylated tubulin. Manipulation of the content of these modifications of tubulin could work as a new strategy to maintain homeostasis of Na+ and K+, and to regulate a variety of functions in which NKA is involved, such as osmotic fragility and deformability of human erythrocytes. The results summarized in this review show that the interaction between tubulin and NKA plays an important role in cellular physiology, both in the regulation of Na+/K+ homeostasis and in the rheological properties of the cells, which is mechanically different from other roles reported up to now.